Familial risk of obstetric anal sphincter injuries: registry‐based cohort study. Issue 7 (26th March 2013) - Baghestan, E; Irgens, LM; Børdahl, PE; Rasmussen, S
<x xml:space="preserve">Abstract</x> Objective To investigate the aggregation of obstetric anal sphincter injuries (OASIS) in relatives. Design Population‐based cohort study. Setting The Medical Birth Registry of Norway from 1967 to 2008. Population All singleton, vertex‐presenting infants weighing 500 g or more. Through linkage by national identification numbers, 393 856 mother–daughter pairs, 264 675 mother–son pairs, 134 889 mothers whose sisters later became mothers, 132 742 fathers whose brothers later became fathers, 131 702 mothers whose brothers later became fathers and 88 557 fathers whose sisters later became mothers were provided. Methods Comparison of women with and without a history of OASIS in their relatives. Main outcome measure Relative risk of OASIS after a previous OASIS in the family. Results The risk of OASIS was increased if the woman's mother or sister had OASIS in a delivery (aRR 1.9, 95% CI 1.6–2.3; aRR 1.7, 95% CI 1.6–1.7, respectively). If OASIS occurred in one brother's partner at delivery, the risk of OASIS in the next brother's partner was modestly increased (aRR 1.2, 95% CI 1.1–1.4). If OASIS occurred in one sister at delivery, the risk of OASIS in the brother's partner was also increased a little (aRR 1.2, 95% CI 1.1–1.4). However, there was no excess occurrence in sisters whose brothers' partners had previously had OASIS (aRR 1.1, 95% CI 0.9–1.3). Conclusions There appears to be increased familial aggregation of OASIS. These risks are stronger through the maternal rather than the paternal line of transmission, suggesting a strong genetic role that shapes aggregation of OASIS within families. These observations must be cautiously interpreted because of bias from unmeasured confounding factors may have impacted the findings.